Controlled Tuning of the Size of Ag-Hydrosol Nanoparticles by Nonstabilized THF and Detection of Peroxides in THF - Šloufová, Ivana (Langmuir : the ACS journal of surfaces and colloids, 2019)
Surface plasmon extinction (SPE) spectra of plasmonic nanoparticles (NPs) are sensitive indicators of their composition, size, shape, interparticle interactions, and of the dielectric constant of their ambient. In this study, rapid changes in SPE spectra of Ag NPs suggesting variations in NP size and concentration were detected after addition of aged tetrahydrofuran (THF). Using time-dependent UV/vis spectroscopy combined with factor analysis, transmission electron microscopy imaging, selected-area electron diffraction, and energy-dispersive X-ray analysis, we observed that an over-limit amount of aged THF fully dissolved Ag NPs with no plasmon recovery. By contrast, an under-limit amount led to incomplete dissolution of Ag NPs and, after reaching the turnover point, to spontaneous recrystallization on residual Ag nuclei, as demonstrated by the SPE band intensity recovery to the original or even higher values. The newly formed Ag NPs were isometric, and their diameter was dependent on the added amount of THF. Furthermore, both Ag NP dissolution and recrystallization were caused by THF peroxides and their reduction products. Therefore, the dissolution of Ag NPs and the resulting hydrosol bleaching may be used as an indicator of the presence of peroxides in THF. Moreover, the reaction of aged THF with Ag NPs can be employed as a tool for tuning the size of Ag NPs in hydrosols